Soil humus-reducing bacteria in the Xisha islands, South China sea: unveiling diversity and predicting functions - Xiao Deng; Saba Najeeb; Kun Liu; Huadong Tan; Yi Li; Chunyuan Wu; Yi Zhang (BMC Microbiology)
Abstract Humic-reducing bacteria (HRB) play crucial roles in various biogeochemical cycles, including carbon (C), nitrogen (N), and sulfur (S) cycles. Tropical reef islands, constituting unique ecosystems, possess distinct soil properties. This study represents the first comprehensive exploration of HRB communities in soil profiles on the Xisha Islands in the South China Sea. Our research aimed to understand their vertical distribution, diversity, and ecological functions. Soil samples collected from different layers (0–12 cm, 12–25 cm, 25–55 cm, and 55–80 cm) on Zhaoshu Island (ZSI), North Island (NI), and Middle Sandbar (MS) were analyzed using High-throughput sequencing and functional annotation of prokaryotic taxa (FAPROTAX). The results demonstrated that Firmicutes was the predominant phylum across all studied reef islands. HRB communities primarily comprised the Firmicutes (60.5–81.7%) and Proteobacteria (18.2–39.3%) phyla. Firmicutes exhibited higher abundance in tropical reef islands than in other habitats, whereas Proteobacteria were less so. The relative abundance of Firmicutes was lower in surface layers, whereas Proteobacteria showed an opposite pattern. Alpha diversity of HRB communities was significantly higher in 0–25 cm than in 25–80 cm depths. Beta diversity in HRB communities’ beta diversity differed significantly between depths of 0–25 cm and 25–80 cm. Soil pH, organic matter, available phosphorus, and five other factors were significantly correlated with the HRB community structure. Further analysis using FAPROTAX corroborated that HRB communities on tropical reef islands primarily functioned in C, Mn, and S cycles, exhibiting significant differences between the 0–25 cm and 25–80 cm depths. These findings deepen our understanding of the relationship between HRB communities and soil environments, offering valuable insights into conserving the Xisha Islands’ ecosystem.